HEIGHT-DIAMETER EQUATIONS FOR BRAZIL NUT INTERCROPPED WITH RUBBER TREE IN THE SOUTH OF MINAS GERAIS - Ribeiro, Sabina Cerruto; Caetano, Aldenir de Carvalho; de Macedo, Renato Luiz Grisi; Dias, Bruna Anair Souto (Floresta, 2014)
Abstract Brazil nut is a worldwide-recognized species due to its nuts, traded around the globe playing an important social and economic role in the Amazon. Several studies published information on issues related to nuts production and effects of seed gathering in the species regeneration. Nonetheless, to our knowledge there are no studies focusing on dendrometric parameters for Brazil nut outside its natural occurrence area. Thus, our study aimed to adjust height-diameter equations for Brazil nut intercropped with rubber tree in the South of Minas Gerais. Four standard models were tested using an ordinary least squares-regression analysis. The goodness-of-fit criteria used were the adjusted coefficient of determination ( 2), the percent standard error of estimate (SEE%) and the residual distribution analysis. The best-fit equation for the estimation of height was from model 1 ( 2 = 0.950;SEE% = 9.768). The adjusted height-diameter equations had comparable 2 and SEE%to other published studies on Brazil nut trees and further species. The adjusted height-diameter equation provided by this study can give support to future forest mensuration and management researches with this species, especially in the South-Central region of Brazil. Keywords: Bertholletia excelsa; height; Amazon. Resumo Equações hipsométricas para castanheira-da-amazônia cultivada em consórcio com seringueira no sul de Minas Gerais. A castanheira-da-amazônia é uma espécie reconhecida mundialmente por sua castanha, que é comercializada no mundo todo e tem um papel social e econômico importante na Amazônia. Diversos estudos publicaram informações sobre questões relacionadas com a produção das castanhas e os efeitos da coleta das mesmas sobre a regeneração dessa espécie. No entanto, até onde vai o nosso conhecimento, não existem estudos que avaliaram parâmetros dendrométricos da castanheira-da-amazônia fora da sua área de ocorrência natural. Assim, este estudo teve como objetivo ajustar equações hipsométricas para castanheira-da-amazônia em consórcio com a seringueira no sul de Minas Gerais. Quatro modelos foram testados usando análise de regressão pelo método dos mínimos quadrados. Os critérios usados para a avaliação do ajuste foram o coeficiente de determinação ajustado ( ), o erro padrão da estimativa (Syx%) e a análise gráfica dos resíduos. A equação de melhor ajuste para a estimativa da altura foi o modelo 1 ( 2 = 0,950; Syx% = 9,768). As equações hipsométricas ajustadas tiveram 2 e Syx% comparáveis a outros estudos publicados para castanheiras-da-amazônia e outras espécies nativas. A equação hipsométrica ajustada neste estudo pode dar suporte para futuras pesquisas de mensuração e manejo florestal dessa espécie, especialmente na região Centro-Sul do Brasil. Palavras-chave: Bertholletia excelsa; altura; Amazônia.